Alaska Plea Bargaining Study, 1974-1976 - Clarke, Stevens H. ([Verlag nicht ermittelbar], 1984)
This study examines the characteristics of criminal offenders as they affect the primary outcomes of their court cases, particularly plea bargaining decisions. The study was conducted in Anchorage, Juneau, and Fairbanks, Alaska, over a two-year period from August 1974 to August 1976. The data were collected from police booking sheets, public fingerprint files, and court dockets. The unit of observation is the felony case, i.e., a single felony charge against a single defendant. Each unit of data contains information about both the defendant and the charge. The variables include demographic and social characteristics of the offender, criminal history of the offender, nature of the offense, evidence, victim characteristics, and administrative factors related to the disposition of the case.